Evaluation of the Efficacy of a Full-Spectrum Low-THC Cannabis Plant Extract Using In Vitro Models of Inflammation and Excitotoxicity - Emily Ross-Munro; Esra Isikgel; Bobbi Fleiss (Biomolecules)
Evidence has accumulated that Cannabis-derived compounds have the potential to treat neuroinflammatory changes present in neurodevelopmental conditions such as autism spectrum disorder. However, research is needed on the specific brain health benefits of strains of whole Cannabis extract that are ready for commercial production. Here, we explore the anti-inflammatory and neuroprotective effects of NTI-164, a genetically unique high-cannabidiol (CBD), low-Δ9-tetrahydrocannabinol extract, and also CBD alone on BV-2 microglia and SHSY-5Y neurons. Inflammation-induced up-regulation of microglial inflammatory markers was significantly attenuated by NTI-164, but not by CBD. NTI-164 promoted undifferentiated neuron proliferation and differentiated neuron survival under excitotoxic conditions. These effects suggest the potential for NTI-164 as a treatment for neuropathologies.